An almost ideal wage database harmonizing the ILO October Inquiry - Daniela Harsch; Jörn Kleinert (Institut für Angewandte Wirtschaftsforschung (IAW), 2011)
The lack of comprehensive, international comparable wage data has been deplored for decades and has constrained the empirical analysis of wage growth and inequality. This is the case although, since 1924, the International Labor Organization (ILO) has conducted an October Inquiry to obtain data on wages worldwide, which leads to an annual wage survey containing data for 161 occupations in over 130 countries. Freeman and Oostendorp (2000) have started a novel project to make use of the October Inquiry, which we update. We provide a documentation about the several steps taken to transfer the data into a comparable and usable form. The data allow analyzing wage growth and inequality in a comprehensive way. In this paper, we describe the way we converted the data and present some results on developments in the wage structure between and within countries and occupations.
Keywords: C31; J31; E24; 330; Wage growth; cross section models; wage structure; Lohnstatistik; Berufsstatistik; Statistische Datenbank; Lohnstruktur; Schätzung; Welt